Kinematic comparison of the seoi-nage judo technique between elite and college athletes - Ishii, T.; Ae, M.; Suzuki, Y.; Kobayashi, Y. (Sports Biomechanics, 2018)
This study sought to identify biomechanical factors that determine fast and skilful execution of the seoi-nage (shoulder throw) technique by comparing kinematics between elite and college judo athletes. Three-dimensional motion data were captured using a VICON-MX system with 18 cameras operating at 250 Hz as three male elite and seven male college judo athletes performed seoi-nage. No significant difference was found in motion phase time of the turning phase between the two groups, indicating that motion phase time is not necessarily a factor contributing quickness in seoi-nage. The maximum relative velocity of the whole body centre of mass along the anterior-posterior direction was significantly greater in the elite athletes (2.74 ± 0.33 m/s) than in the college athletes (1.62 ± 0.47 m/s) during the turning phase (p = 0.023). The overall angular velocity of the body part lines, particularly the arm line, tended to be greater in the elite athletes (p = 0.068). The results imply that the velocity of the thrower relative to the opponent in the forward drive and turning motion reflects high skill seoi-nage. Coaches should recognise the relative forward velocity as a factor that may contribute to a successful seoi-nage when teaching the judo throw technique. ABSTRACT FROM AUTHOR